Teaching Grammar: The Intersection of Teacher Stated Beliefs and Classroom Implementation - Widagsa, Rudha; Rahmawan, Andi; Tria Agustin, Dery; Andrea, Andrea (LET: Linguistics, Literature and English Teaching Journal, 2024)
This study investigates the intersection between teachers’ stated beliefs regarding grammar instruction and their actual classroom practices, focusing on two experienced English teachers in Yogyakarta, Indonesia. While prior research underscores the influential role of teachers' beliefs in shaping instructional approaches, discrepancies between these beliefs and classroom implementation are frequently observed. This qualitative case study involved two English teachers from a junior high school in Yogyakarta who have completed their undergraduate degrees in English education and have over ten years of teaching experience. Data were collected through semi-structured interviews, classroom observations, and document analysis to explore how teachers' beliefs about teaching grammar align or diverge from their practices. The findings reveal inconsistencies, demonstrating that while both teachers express a preference for implicit, communicative approaches, practical challenges such as large class sizes, curriculum demands, and varied student proficiency often necessitate the use of explicit instruction methods. These results support existing literature that highlights contextual factors as mediators between beliefs and practices. The study emphasizes the need for reflective practices and tailored professional development programs that help teachers align their instructional strategies with their beliefs. This alignment can enhance instructional effectiveness and foster a more cohesive learning environment. Future research should further investigate how professional development and reflective practices can support teachers in bridging the gap between their beliefs and classroom methodologies.